Keeping it Clean: Cleaning Bathrooms, Sink, Bathtub, Shower, Toilet - Mary N. Harrison (EDIS)
Every family member can help keep the bathroom clean and in good condition. Some chores need to be done daily, others weekly. This document is FCS5232-04, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised December 2005.